Mengoptimalkan Potensi PPN Merauke: Studi Kasus Strategi Peningkatan Kinerja Pelabuhan Perikanan di Kawasan Timur Indonesia - Chalvyn Silasa Pakidi; Astaman Amir (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the potential and strategic role of the Merauke Archipelago Fisheries Port (PPN) in the national fishing port system, evaluate the performance improvement strategies that have been implemented, and provide data-based recommendations to optimize port performance. The method used is a qualitative case study supported by descriptive quantitative data. Data were collected through in-depth interviews with 25 purposively selected informants, direct observation, document studies, and user satisfaction level surveys. The analysis was carried out thematically for qualitative data and descriptively for quantitative data, with triangulation to increase the validity of the findings. The results of the study indicate that PPN Merauke has strategic potential as the main node for fisheries distribution and export in eastern Indonesia, but its performance is still constrained by limited infrastructure, low integration of managerial, technical, and policy governance, and suboptimal user satisfaction. The strategies that have been implemented, such as service digitalization and infrastructure improvements, have not been fully effective due to the lack of multi-party synergy. This study recommends the need for an integrated approach based on local potential to support the sustainability and competitiveness of ports. These findings are expected to be a reference for policy makers and stakeholders in the development of fishing ports in underdeveloped but potential areas.